Dampak Dualisme Otonomi Daerah: Pengurangan Kemiskinan Jangka Panjang vs Peningkatan Jangka Pendek di Provinsi Bali, Indonesia: Analisis VECM: Universitas Islam Negeri Alauddin Makassar, Universitas Hasanuddin (Jurnal Ekonomi dan Kebijakan Pembangunan, 2025)
This study examines the complex dynamics between regional autonomy and poverty in Bali, Indonesia (2002–2024), testing the hypothesis that decentralization reduces poverty despite institutional capacity constraints. Using quarterly data, we apply Vector Autoregression (VAR) and Vector Error Correction Models (VECM) to analyze short-term interactions and long-term equilibrium between fiskal autonomy (measured by local revenue-to-budget ratio) and multidimensional poverty. Lag selection follows rigorous criteria (AIC, SC, HQ), with diagnostic checks for stability (AR roots) and causality (Granger). Findings are Long-term success: A 1% rise in autonomy reduces poverty by 41.3% (VECM: coint. eq. = -41.307, t-stat = -4.73). Short-term anomaly, poverty temporarily increases by 0.4% after autonomy shocks (IRF) due to governance failures, with error correction mechanisms exacerbating poverty (ECT = +0.011, t-stat = 4.00). Autonomy exhibits strong inertia (IRF persistence >5 quarters), while poverty self-perpetuates (hysteresis). Granger tests confirm autonomy and poverty are independent in the short run. Decentralization requires preconditions: anti-corruption frameworks and adaptive capacity building. Asymmetric policies are needed, high-capacity regions benefit from fiskal autonomy, low-capacity regions require central oversight with safety nets (e.g., conditional cash transfers).